2012
DOI: 10.1098/rsif.2011.0825
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution microrheology in the pericellular matrix of prostate cancer cells

Abstract: Many cells express a membrane-coupled external mechanical layer, the pericellular matrix (PCM), which often contains long-chain polymers. Its role and properties are not entirely known, but its functions are believed to include physical protection, mechanosensing, chemical signalling or lubrication. The viscoelastic response of the PCM, with polysaccharides as the main structural components, is therefore crucial for the understanding of its function. We have here applied microrheology, based on optically trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…19 It has been reported that the PCM can reduce the ability of small molecules such as DNA 18,26 and sodium ions 27 to penetrate into cells. Thus, it is surprising that the PCM can recruit AuNPs and assist their cellular internalization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 It has been reported that the PCM can reduce the ability of small molecules such as DNA 18,26 and sodium ions 27 to penetrate into cells. Thus, it is surprising that the PCM can recruit AuNPs and assist their cellular internalization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In some cases this failure is dramatic[35]. Therefore, passive microrheology for characterizing the pericellular space has been limited to either detection of the formation of a hydrogel, dissolution of a hydrogel[36], or ECMs that are orders of magnitude softer than in vivo ECMs[37,38]. …”
Section: Resultsmentioning
confidence: 99%
“…Visualization of the HA pericellular layer is less straightforward. There is a host of literature describing the use of fluorescent dyes to label the HA pericellular layer for endothelial cells (2,12,15,45), in which the HA layer has a rather well-defined boundary. Imaging of the HA layer on fibroblasts seems not to be as straightforward as on endothelial cells.…”
Section: Resultsmentioning
confidence: 99%